Moderators of workplace aggression: The influences of social support and training - Brown, Valerie M.; Loh, Jennifer M. I; Marsh, Nigel V.* (Cambridge University Press, 2012)
Reception and administrative employees may be particularly vulnerable to patient aggression in mental health services. This study examined whether satisfaction with social support and primary aggression training moderated the effects of perceived aggression on psychological distress and somatic symptoms in a sample of 101 employees. The biophysical model of threat and challenge, the stressor-stress-strain model, and the stress-buffering hypothesis served as theoretical frameworks. Results showed perceived aggression correlated positively with psychological distress, but not with somatic symptoms. Significant interactions were found for social support (buffering effect) and training (interaction effect) for somatic symptoms, but not for psychological distress. It is suggested that, for somatic symptoms, the moderation effects of social support and training on perceived aggression involve similar mechanisms (increased knowledge, self-esteem, perceived control, coping capacity). These findings provide support for the benefits of staff training and the incorporation of knowledge-based components in training programs.